Surface‐Electron Coupling for Efficient Hydrogen Evolution. (4th October 2019) - Fu, Weiwei; Wang, Yanwei; Hu, Jisong; Zhang, Huijuan; Luo, Ping; Sun, Fang; Ma, Xinguo; Huang, Zhengyong; Li, Jian; Guo, Zaiping; Wang, Yu
Abstract: Maximizing the activity of materials towards the alkaline hydrogen evolution reaction while maintaining their structural stability under realistic working conditions remains an area of active research. Herein, we report the first controllable surface modification of graphene(G)/V8 C7 heterostructures by nitrogen. Because the introduced N atoms couple electronically with V atoms, the V sites can reduce the energy barrier for water adsorption and dissociation. Investigation of the multi‐regional synergistic catalysis on N‐modified G/V8 C7 by experimental observations and density‐functional‐theory calculations reveals that the increase of electron density on the epitaxial graphene enable it to become favorable for H* adsorption and the subsequent reaction with another H2 O molecule. This work extends the range of surface‐engineering approaches to optimize the intrinsic properties of materials and could be generalized to the surface modification of other transition‐metal carbides. Abstract : Kleines N, große Wirkung : Die kontrollierbare Modifizierung von Graphen/V8 C7 ‐Heterostrukturen durch Stickstoff wird vorgestellt. Aufgrund von Veränderungen in der elektronischen Struktur einzelner Teile der modifizierten Heterostruktur zeigt sie eine außergewöhnliche Leistungsfähigkeit in der alkalischen Wasserstoffentwicklung – die effizienteste Katalyse dieser Art, die bislang für Übergangsmetallcarbide bekannt ist.